2010
DOI: 10.2353/ajpath.2010.090746
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Profile of Focal Segmental Glomerulosclerosis from Formalin-Fixed, Paraffin-Embedded Tissue

Abstract: Focal segmental glomerulosclerosis (FSGS) is a common form of idiopathic nephrotic syndrome defined by the characteristic lesions of focal glomerular sclerosis and foot process effacement; however, its etiology and pathogenesis are unknown. We used mRNA isolated from laser-captured glomeruli from archived formalin-fixed, paraffin-embedded renal biopsies, until recently considered an unsuitable source of mRNA for microarray analysis, to investigate the glomerular gene expression profiles of patients with primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 50 publications
4
89
1
1
Order By: Relevance
“…This is a striking finding because, in the latter study, lasermicrocaptured glomerular tufts were analyzed, and the number of PECs should be limited. This finding by Hodgin et al 30 can be explained by migration of PECs onto the glomerular tuft and suggested that ectopic presence of PECs on the glomerular tuft can be used as a diagnostic marker for FSGS. ajp.amjpathol.org -The American Journal of Pathology…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This is a striking finding because, in the latter study, lasermicrocaptured glomerular tufts were analyzed, and the number of PECs should be limited. This finding by Hodgin et al 30 can be explained by migration of PECs onto the glomerular tuft and suggested that ectopic presence of PECs on the glomerular tuft can be used as a diagnostic marker for FSGS. ajp.amjpathol.org -The American Journal of Pathology…”
Section: Discussionmentioning
confidence: 87%
“…In that study, the researchers performed molecular profiling on laser-captured glomerular tufts from patients with FSGS and collapsing glomerulopathy and compared the profiles to those of patients with MCD. 30 Interestingly, approximately 46% (11 of 24) of the genes listed to be the highest up-regulated genes in the FSGS þ collapsing glomerulopathy group are normally expressed by PECs. This is a striking finding because, in the latter study, lasermicrocaptured glomerular tufts were analyzed, and the number of PECs should be limited.…”
Section: Discussionmentioning
confidence: 99%
“…RNA of a very high quality was obtained (Supplemental Figure 1A). 21,22 RNA of sufficient quality for amplification and hybridization was obtained from 30 patients with ANCA-associated crescentic GN and 12 controls (preimplantation kidney biopsies of living or deceased kidney donors). The patient characteristics and clinical data of the group of patients from whom RNA was isolated were not significantly different from those from the remaining patients included in the study (Supplemental Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…As more PECs invade the glomerular tuft, extracellular matrix proteins continually and progressively accumulate beyond this original site, ultimately leading to an advanced sclerotic lesion of FSGS. More recently, transcriptomic studies add further evidence for a role of PECs in matrix accumulation, wherein an abundance of genes considered 'PEC-specific' were detected in areas of sclerosis in human glomeruli [40]. Thus, one current view underlying the mechanism of segmental scarring in FSGS is that the extracellular matrix accumulation likely arises from two sources: injured podocytes and activated PECs.…”
Section: Parietal Epithelial Cells and Glomerular Scarringmentioning
confidence: 99%